The Anishinaabe Worldview and the Child Reader in Louise Erdrich's The Birchbark House series - Sparks, Angela Joy (2019)
Louise Erdrich is an award-winning Anishinaabe-American author, whose works of fiction have attracted a significant body of scholarly interest. To date, her output of children's fiction has received comparatively less critical attention. This thesis is the first study to consider The Birchbark House series (published between 1999 and 2016) as a whole unit, in order to demonstrate its importance as a contributor to the perpetuation of Anishinaabe values amongst both Indigenous and settler children, and as a counter-hegemonic narrative. This thesis takes as its starting point the development of children's literature as a field of scholarly enquiry, using existing theoretical frameworks to situate The Birchbark House series within the discourse surrounding children's and young adult literature. The thesis then traces the Anishinaabe worldview through the novels by considering key themes that emerge from Anishinaabe and Native studies as markers of Indigenous culture. The contribution to knowledge of this thesis lies in drawing together the critical fields of Native Studies and Children's Literature. By examining The Birchbark House series through the themes of land/environment, home, family, and storytelling, this thesis demonstrates the ways in which Erdrich privileges an Anishinaabe worldview, and in doing so shows how Erdrich's children's fiction interacts with and belongs to her wider body of work. The key findings of this thesis relate to the child reader and the development of indigenous methodologies. Erdrich's novels are central to the rapid growth of Anishinaabe-authored children's and young adult literature, and embedded within a wider cultural renaissance which is contributing to growing activism and widespread awareness of Indigenous cultural and political issues. This in turn warrants a reassessment of the methodologies underpinning the critical study of emerging Indigenous children's literature, building on the existing development of decolonising and indigenous methodologies within Anishinaabe ...